Recurrent Scar Endometriosis in A Young Lady of 23 Years - Siddiquee, Fayela Subrun; Sen, Shila; Rahman, Md Mahbubur (Journal of Bangladesh Society of Physiologist, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> A young lady of 23 years was admitted in the Gynaecology & Obstetrics department of the Community Based Medical College Hospital, Bangladesh with sensation of irregular fixed mass in left side of lower anterior abdominal wall in and around her previous scar for 01 year and periodic pain in that mass for 8 months during menstruation. Some times she felt colicky pain in lower and umbilical region, not related with menstruation. This lady was married for 6 years and para - 01 (still birth) and delivery was done by lower uterine caesarean section 4Â½ years back, and developed such mass for a few months after lower uterine caesarean section. This mass was excised 3Â½ years back. On the basis of history , clinical findings, ultra sonongrphic finding and histopathological report, this case was diagnosed as scar endometriosis. She was also getting post operatively synthetic androgen for 6 months (400 mg daily). She again developed that mass 01 year after operation. Now she is almost free from pelvic pain by using synthetic androgen (Denazol) and is advised for pregnancy with assisted by reproductive technology. All current therapies offer relief but cannot assure cure of recurrent scar endometriosis. Even after definitive surgery, endometriosis may recur. Definitive surgical treatment followed by long term oestrogen therapy yields better results. However the future treatment options should greatly improved upon what is offered now. Key Words: Endometriosis; scar; pelvis; pain Â Â doi: 10.3329/jbsp.v3i0.1804 J Bangladesh Soc Physiol.2008 Dec;(3):85-89.